Variation in leaf biomass and fruit output of Juniperus indica along an elevation gradient in north-central Nepal - Chapagain, A.; Chaudhary, R. P.; Ghimire, S. K. (Banko Janakari, 2017)
Biomass and reproductive output are important functional traits that influence aspects of plant performance. Measurements of these attributes by harvesting plant parts are often destructive and impractical. Therefore, non-destructive methods, based on allometric relationships, have been recommended for measuring plant biomass and reproductive output, particularly in the ecosystems where plant harvesting is not very practical or feasible. Here, we assessed the variation in the traits related to vegetative and reproductive performance (including plant height, trunk diameter, canopy area, leaf biomass and number of fruits set) among populations of Juniperus indica distributed along an elevation gradient in Manang district of the north-central Nepal, and finally determined the allometric relationships addressing the leaf biomass and the fruit output. The distribution range of J. indica was divided into lower- (3,350–3,580 m), mid- (3,650–3,880 m) and higher- (3,950–4,250 m) elevation classes where we made 54 sample plots of 10 m × 10 m size. In each plot, we recorded the number of individuals of J. indica classifying into seedling, juvenile and mature classes, and measured their vegetative traits and fruit output. Trunk diameter, leaf dry-weight and fruits set parameters spatially varied within the same elevation class. The individuals at the lower-elevation were larger in vegetative size with larger- trunk, height and canopy area, and produced higher leaf biomass and greater number of fruits as compared to those produced by the individuals situated at the mid- and higher-elevations. The regression analysis showed the strongest relationship between the canopy area and the leaf biomass. Thus, the use of outer canopy dimension is found to be the best option for estimation of leaf biomass of J. indica using non-destructive method. Banko Janakari, Vol. 27, No. 1, 2017, page: 3-10